2020
DOI: 10.15587/1729-4061.2020.201819
|View full text |Cite
|
Sign up to set email alerts
|

Engineering method for determining rational fire protection parameters of warehouses

Abstract: 38 4) instant inclusion of smoke protection systems (smoke and heat removal system with opening mechanism) 5) automatic opening of evacuating doors; 6) instant inclusion of an automatic fire extinguishing system for objects.At the present stage, when installing fire protection systems (FPS) at the facility, a problem arises that they do not take into account for the facility, in order to reduce the cost of purchasing fire protection systems, the allowable service area for each device in the system. This approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The authors of work [2] proposed an engineering method for determining the number of fire detectors in closed premises of warehouses and logistics centers. The simulation results showed that in order to ensure the reliability of fire protection systems, it is necessary to increase the number of fire detectors several times compared to the normative number.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of work [2] proposed an engineering method for determining the number of fire detectors in closed premises of warehouses and logistics centers. The simulation results showed that in order to ensure the reliability of fire protection systems, it is necessary to increase the number of fire detectors several times compared to the normative number.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Ensuring an acceptable level of fire safety in warehouse buildings and structures is an important task. The number of large warehouse facilities is growing, logistics centers are being built with areas reaching tens of thousands of m 2 . Statistics indicate that over the past decade, the number of fires at such facilities has quadrupled.…”
Section: Introductionmentioning
confidence: 99%